2001
DOI: 10.1155/2001/469630
|View full text |Cite
|
Sign up to set email alerts
|

DNA Ploidy and S‐Phase Fraction in Carcinoma of the Gallbladder Related to Histopathology, Number of Gallstones and Survival 1

Abstract: Gallstones are a risk factor for the development of gallbladder cancer. We studied DNA ploidy and cell cycle composition by flow cytometry in archival specimens from 52 gall bladder carcinomas in relation to histopathological grade, tumour stage, gallstone number and survival. 69% of the gallbladder carcinomas showed aneuploidy. All tumours with single stones (N=11) were aneuploid while only 61% of tumours with multiple stones (N=41) were aneuploid (p=0.002). DNA aneuploidy was related to increase in T‐categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Nuclear pleomorphism has long been appreciated as a prognostic indicator in many cancers, and is routinely evaluated as part of the grading of sarcoma, breast carcinoma, and other malignancies. Although studies in a variety of carcinomas showed that nuclear pleomorphism correlated with increased DNA content (ploidy) , the more precise molecular correlates of pleomorphism are not well understood. The Sarcoma TCGA Analysis Working Group used image analysis methods to assess the relationships between nuclear pleomorphism, clonality, and genomic instability (Figure A).…”
Section: Computational Pathology In Tcgamentioning
confidence: 99%
“…Nuclear pleomorphism has long been appreciated as a prognostic indicator in many cancers, and is routinely evaluated as part of the grading of sarcoma, breast carcinoma, and other malignancies. Although studies in a variety of carcinomas showed that nuclear pleomorphism correlated with increased DNA content (ploidy) , the more precise molecular correlates of pleomorphism are not well understood. The Sarcoma TCGA Analysis Working Group used image analysis methods to assess the relationships between nuclear pleomorphism, clonality, and genomic instability (Figure A).…”
Section: Computational Pathology In Tcgamentioning
confidence: 99%
“…It has been reported that with the process of tumor development, a shift in karyotypes can be explained by successive loss or gain of chromosomes combined with aberrant variation of genes involved in cell cycle regulation, resulting in cell populations with advantage of growth. [ 33 ] Treatment was also another factor leading to the karyotype shift. Agents that target the spindle apparatus, DNA replication, topoisomerases, hypoxia, proteasome, histone deacetylase, and cell cycle kinases were reported to participate in generating cells with aneuploid by increasing the risk of chromosomal instability (CIN) during mitosis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because our qPCR analysis revealed gain of copies of both MYC and TP53, we cannot exclude the possibility of several chromosome aneuploidies or even polyploidy in gallbladder carcinoma cells. Alterations in chromosome copy number were previously reported in gallbladder carcinomas [7,[22][23][24].…”
mentioning
confidence: 99%